Circularly polarized radio emission from the repeating fast radio burst source FRB 20201124A. Issue 3 (14th March 2022) - Kumar, P; Shannon, R M; Lower, M E; Bhandari, S; Deller, A T; Flynn, C; Keane, E F
ABSTRACT: The mechanism that produces fast radio burst (FRB) emission is poorly understood. Targeted monitoring of repeating FRB sources provides the opportunity to fully characterize the emission properties in a manner impossible with one-off bursts. Here, we report observations of the source of FRB 20201124A, with the Australian Square Kilometre Array Pathfinder (ASKAP) and the ultra-wideband low (UWL) receiver at the Parkes 64-m radio telescope ( Murriyang ). The source entered a period of emitting bright bursts during early 2021 April. We have detected 16 bursts from this source. One of the bursts detected with ASKAP is the brightest burst ever observed from a repeating FRB source with an inferred fluence of 640 ± 70 Jy ms. Of the five bursts detected with the Parkes UWL, none display any emission in the range 1.1–4 GHz. All UWL bursts are highly polarized, with their Faraday rotation measures (RMs) showing apparent variations. We obtain an average RM of −614 rad m −2 for this FRB source with a standard deviation of 16 rad m −2 in the UWL bursts. In one of the UWL bursts, we see evidence of significant circularly polarized emission with a fractional extent of 47 ± 1 per cent. Such a high degree of circular polarization has never been seen before in bursts from repeating FRB sources. We also see evidence for significant variation in the linear polarization position angle in the pulse profile of this UWL repeat burst. Models for repeat burst emission will need to account for the increasing diversity in the burst polarization properties.